Long-term successional changes in peatlands of the Hudson Bay Lowlands, Canada inferred from the ecological dynamics of multiple proxies. (January 2015) - Hargan, Kathryn E; Rühland, Kathleen M; Paterson, Andrew M; Holmquist, James; MacDonald, Glen M; Bunbury, Joan; Finkelstein, Sarah A; Smol, John P
Peatlands in northern Ontario, Canada, archive multiple biological indicators, including macrofossils, algae, testate amoebae, and pollen. These proxies can provide insights concerning the timing and nature of long-term climatic and environmental changes. The Hudson Bay Lowlands (HBL) of central Canada contain one of Earth's largest continuous peatland complexes, and thus comprehensive spatial and temporal studies are needed to understand the implications of climate change on carbon cycling. Diatom assemblages were examined in three cores retrieved from ombrotrophic bogs across two Canadian terrestrial ecozones. Comparisons were made with testate amoebae and macrofossil data previously analyzed from these cores, as well as with regional pollen records from surrounding peatlands. From ~2000 to ~600 cal. BP, changes in diatom composition likely reflect hydrosere succession within the peatland, including fluctuations in connectivity to the water table and pH changes. From ~600 cal. BP to present, the synchronous timing of changes in diatoms and testate amoebae are tracking drying conditions and subsequent microhabitat variations that occur within bogs. It is possible that diatoms are tracking subtle changes in the stability of peat microforms including bog hollows and hummocks, highlighting their sensitivity to small chemical change, whereas testate amoebae are tracking the lowering of a peatland water table and subsequent drying of the peatland. The use of multiple proxies provides a more holistic approach to interpreting past ecological succession and responses to climate within peatlands. When present and well preserved, diatoms can be applied to track drying conditions in bogs, in terms of both hydrosere succession and present climatic change.